The Relationship of the Algerian Francophone Novel with Colonial Discourse: A Reading of Selected Models - Bouratoua, Mouna Bechlem (Dirasat: Human and Social Sciences, 2024)
Objectives: The Algerian novel, written in French, emerged during the colonial period, prompting its natural composition in the language of the colonizer. This choice was particularly significant as the colonizer aimed to eradicate Arab culture and restrict education to their language. Despite the context of colonial dominance, the novel persisted even after independence. Thus, this research seeks to explore the relationship between the discourse of Francophone novelists and colonial discourse. Methods: The research selected two novels from the third millennium: The Preference of Night over Day by Yasmina Khadra and Meursault’s Counter-Investigation by Kamal Daoud. Through a cultural analysis of these novels, the study aims to investigate the formation of Algerian identity. It explores whether these two novels resisted colonial subjectivation or inadvertently reproduced it, examining their language and narrative styles. Results: The analysis reveals that both novels under study exhibit a reliance on colonial discourse, contributing to its novelistic reproduction. They juxtapose the colonial era with a nostalgic narrative and depict the period of independence, including its challenges and the subsequent black decade in Algeria. This depiction serves to perpetuate colonialist stereotypes of the original. Conclusions: The relationship between the Algerian Francophone novel and colonial discourse varies between counter-narrative and reproduction, with distinctions evident from one novel to another. The research suggests approaching Francophone novels with a conscious reading that delves into the layers of the text. This approach aims to unveil the unique aesthetics and perspectives defining each text and its connection to colonial discourse.